Soft Power - Panayides, Angelos (My University, 2026)
Poster I created for my participation in the 4th Emirates International Poster Festival (EIPF) held in Dubai in 2022. The event took place in Dubai and it’s an initiative of the Cultural and Scientific Association (NADWA) in Dubai to expand creative expression and to promote graphic design practice and creative thinking in the MENA region. In its 4th edition EIPF draws inspiration from the “UAE Centennial 2071“, a future-oriented and human-centric plan that calls for investments in the future and improving quality of life